Effect of composition on the structural development and electrical conductivity of NiO-GDC composites obtained by one-step synthesis - Nascimento, Rubens Maribondo do (2021)
NiO-C0.9Gd0.1O1.95 (NiO-GDC) composites obtained using a chemical route (one-step synthesis) were characterized by thermal analysis, X-ray diffraction (XRD), scanning electron microscopy (SEM) and impedance spectroscopy (between 300 and 650 °C in air). Rietveld refinement of XRD data indicated that synthesized powders are ultrafine and the crystallite size of the GDC phase decreases with increasing NiO content. The relative density of sintered samples is influenced by the NiO content, but easily brought to values above 95% after sintering at 1450–1500 °C. NiO-GDC composites exhibited homogeneous phase distribution and grain size often lower than 1 μm. With 30–40 wt% NiO this phase dominates the overall electrical conductivity of NiO-GDC. The combination of grain size, conductivity and microstructural characteristics shows the efficacy of the adopted processing route to obtain high quality Ni-GDC cermet precursors